2018
DOI: 10.1186/s12888-018-1587-0
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment as a mediator of suicide crises

Abstract: BackgroundPrior research has validated the construct of a suicide crisis syndrome (SCS), a specific psychological state that precedes and may precipitate suicidal behavior. The feeling of entrapment is a central concept of the SCS as well as of several other recent models of suicide. However, its exact relationship with suicidality is not fully understood. In efforts to clarify the exact role of entrapment in the suicidal process, we have examined if entrapment mediates the relationship of other components of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 53 publications
8
39
0
3
Order By: Relevance
“…The centrality of entrapment (Criterion A) to the syndrome is supported by the strong performance of this single symptom. This is consistent with contemporary theories of suicidality such as Galynker's Narrative Crisis model (Galynker, ) and the threeā€step theory of Klonsky and May (Bagge, Littlefield, & Glenn, ; Klonsky & May, ) which posit the experience of entrapment as the central component of the presuicidal mental state, and our recent finding that entrapment severity mediates the influence of other SCS symptoms on postdischarge suicide risk (Li et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…The centrality of entrapment (Criterion A) to the syndrome is supported by the strong performance of this single symptom. This is consistent with contemporary theories of suicidality such as Galynker's Narrative Crisis model (Galynker, ) and the threeā€step theory of Klonsky and May (Bagge, Littlefield, & Glenn, ; Klonsky & May, ) which posit the experience of entrapment as the central component of the presuicidal mental state, and our recent finding that entrapment severity mediates the influence of other SCS symptoms on postdischarge suicide risk (Li et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…Although at present entrapment remains the preferred term for Criterion A because of its acceptability and familiarity, there is some evidence that it is not entirely accurate. First, recent studies have identified emotional pain to be most highly correlated with entrapment (Galynker et al, ; Li et al, ). Second, a network analysis of the SCS (Blochā€Elkouby et al, unpublished data) has established that entrapment is closely linked to emotional pain.…”
Section: Suicide Crisis Syndromementioning
confidence: 99%
“…Most contemporary theories of suicide derive from an escapeā€based conceptualization of the suicidal process (Baumeister, ; Gilbert & Allan, ; Li et al., ; O'Connor, ; Williams & Pollock, ). In this conceptualization, suicide represents an escape behavior and thus suicide ideation a formulation of an escape strategy (Li et al., ). This, however, leaves unasked and unanswered the question of how suicide might enter a person's consciousness in order to be selected as an escape strategy.…”
Section: Discussionmentioning
confidence: 99%